Penatalaksanaan Gangguan Muskuloskeletal dan Gangguan Fisik Pengrajin Keripik Kota Cilegon Banten - Yosephin Sri Sutanti; Susanty Dewi Winata; Yusuf Handoko; Erdy Techrisna (Universitas Katolik Soegijapranata, 2020)
Cilegon City is a pilot city in occupational health services by the Indonesian Ministry of Health in 2010 and until now has been used as an indicator of the success of national occupational health, especially the informal sector. Informal sector workers need attention because the amount is greater than the formal sector but assistance is not optimal. One of them is chips craftsmen. It is hoped that the workers / craftsmen of chips in Cilegon City can work comfortably, healthily, safely, and productively and avoid the diseases caused by their work. In general, the purpose of this service is to develop a more complete and comprehensive understanding of the assisted subjects (partners) to (1) to understand the importance of occupational health and safety by prioritizing ergonomic work principles, (2) increasing knowledge, skills, work attitudes healthy, safe, and comfortable in working, (3) raising awareness and increasing awareness of assisted subjects to be willing to change in the management of a quality work environment, (4) increasing good understanding in the governance of the ergonomic work environment of the chips industry.